Analysis of Cable Part Defects in DL02 Identical E-KTP Reader with Failure Mode and Effect Analysis (FMEA) Approach at PT X - Yulianti, Dini; Diniyah, Annisa Nurfalah (Sainteks: Jurnal Sain dan Teknik, 2025)
PT X produces and sells the e-KTP Reader, specifically the “Identik DL 02” model, which is an electronic reader device for the Indonesian electronic ID card (KTP-el). A quality issue was found in this product, particularly in the cable parts, where a high number of defects occurred. The defective parts included four types of cables: fingerprint cable, chipset cable, on-off button cable, and battery cable. To analyze these defects, the Failure Mode and Effect Analysis (FMEA) method was applied. FMEA is a robust risk assessment method that evaluates potential risks in the design, production, and service stages of a company’s operations, aiming to reduce or eliminate such risks. The goal of FMEA is to ensure that products meet customer requirements, analyze product characteristics from the design phase, identify the causes and effects of failures, determine types of failures, and establish corrective actions to eliminate them. In this study, two tools from the seven quality tools were used: the Fishbone diagram and Pareto chart. The Fishbone diagram was used to identify cause-and-effect relationships for cable part defects, while the Pareto chart was employed to analyze processed data. Based on the FMEA calculation, the chipset cable was identified as the component with the highest potential defects. The most critical defect was found in the PVC insulation of the chipset cable, with the highest Risk Priority Number (RPN) value of 1,060. The main contributing factor was equipment, which had an RPN value of 385.